2018
DOI: 10.3390/land7010030
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Climate Smart Agriculture and Its Determinants of Practice in Ghana: A Case of the Cocoa Production System

Abstract: Agriculture in Africa is not only exposed to climate change impacts but is also a source of greenhouse gases (GHGs). While GHG emissions in Africa are relatively minimal in global dimensions, agriculture in the continent constitutes a major source of GHG emissions. In Ghana, agricultural emissions are accelerating, mainly due to ensuing deforestation of which smallholder cocoa farming is largely associated. The sector is also bedevilled by soil degradation, pests, diseases and poor yields coupled with poor agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 18 publications
3
42
2
1
Order By: Relevance
“…Agricultural technology implementation is influenced by much more than the socioeconomic characteristics of the farmers. Despite past studies identifying the determinants of technology adoption or adaptation in agriculture [7,[19][20][21], there are still variations which can only be explained by the exogenous factors that were not captured by models of past studies focusing on characteristics of farmers when analyzing the determinants of adoption or technology transfer. This line of thinking deviates from the conventional approach that focuses on the inherent characteristics of the technologies or practices which could be of significant influence on adoption or transfer [3].…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Agricultural technology implementation is influenced by much more than the socioeconomic characteristics of the farmers. Despite past studies identifying the determinants of technology adoption or adaptation in agriculture [7,[19][20][21], there are still variations which can only be explained by the exogenous factors that were not captured by models of past studies focusing on characteristics of farmers when analyzing the determinants of adoption or technology transfer. This line of thinking deviates from the conventional approach that focuses on the inherent characteristics of the technologies or practices which could be of significant influence on adoption or transfer [3].…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…The speed of the changes taking place and the negative impacts of many drivers, with no immediate solutions being evident, as well as limited existing opportunities, resulted in pessimism regarding how the younger generation is going to cope in the future. However, a few of the studies also showed how younger farmers were more likely to adopt new farming approaches and how youth, that have been working in towns and cities, may bring home new ideas with the potential for innovation (e.g., Akrofi-Atitianti et al [16], Mango et al [17], Östberg et al [19]). The next generation, who are likely to face some of the greatest impacts of climate change, are rarely included in the type of research covered in this issue's articles.…”
Section: Complex Drivers Of Change and Implicationsmentioning
confidence: 99%
“…This requires working closely with affected people and communities and allowing space for local definitions of concepts such as poverty or wealth and local expressions of changes and their impacts. Good examples of this include the importance of farmer-to-farmer support and learning in the practice of Climate Smart/ Agroecology farming amongst Ghana cocoa producers (Akrofi-Atitianti et al [16]) and the need to understand traditional forms of land access in Samburu, Kenya, which are based on values of reciprocity and trust (Pas [13]). Further, Östberg et al [19] highlight the role of local entrepreneurs and community initiatives in creating the opportunity for 'change from within' as important factors in stimulating the local economy and improving opportunities for livelihood security in their study in Tanzania.…”
Section: Unpacking Responses and Uptake Of 'Solutions'mentioning
confidence: 99%
See 2 more Smart Citations